Avian mycobacteriosis in a naturally infected captive nocturnal curassow (Nothocrax urumutum) - Silva, Laice Alves da; Carvalho, Thaynara Parente de; Oliveira, Ayisa Rodrigues; Santos, Daniel Oliveira dos; Santana, Clarissa Helena; Soares Neto, Lauro Leite; Pereira, Fernanda Mara Aragão Macedo; Gonçalves, Ana Beatriz Portes; Correia, Vitória Gavião Carvalho; Santos, Renato Lima (Brazilian Journal of Veterinary Pathology, 2022)
A senile female nocturnal curassow (Nothocrax urumutum) kept under human care was found dead. Grossly, the lungs were congested and had a nodule with 2.0 cm in diameter adhered to the left lung. Histologically, there were multifocal to coalescent areas of necrosis characterized by deposition of amorphous and eosinophilic material with large amount of cellular debris, surrounded by numerous epithelioid macrophages, multinucleated Langhans giant cells, occasional lymphocytes and plasma cells. Ziehl-Neelsen stained sections demonstrated myriad of intralesional alcohol-acid resistant bacilli (BAAR). DNA extracted from lung samples were evaluated by nested polymerase chain reaction resulting in mycobacterial DNA identification. This is the first reported case of mycobacteriosis in a nocturnal curassow.